Genetic variation and structure change when producing and using mixed‐source seed lots for restoration. Issue 3 (6th September 2021) - Kucera, Katherine F.; Fant, Jeremie B.; Jensen, Scott; Landeen, Melissa; Orr, Emily; Kramer, Andrea T.
Abstract : Large‐scale ecological restoration efforts increasingly require large quantities of genetically diverse seeds adapted to a range of potential sites. To meet this demand, there is a growing emphasis on mixing multiple, regionally sourced source populations in production settings to produce large quantities of genetically diverse seeds. However, because few empirical studies are available, it is unclear how source population representation and genetic diversity shift through production and restoration use of mixed‐source seed lots. We used neutral genetic markers and assays of variation in seed germination requirements to investigate how genetic diversity and source population representation shift following the use of a mixed‐source seed lot to establish a seed production field and 10 restoration sites. Our mixed‐source seed lot contained 19 source populations of the perennial forb, Penstemon pachyphyllus, from six mountain ranges in the Great Basin, U.S.A. We found that, while populations from all six mountain ranges used in the mixed‐source seed lot were present in production and restoration sites, representation of each source mountain range shifted unpredictably. Populations from one mountain range were particularly overrepresented at the production site relative to its composition in the original seed mix. We also found that, despite using the same mixed‐source seed lot for production and restoration sites, resulting source population composition varied greatly, suggesting that local conditions favored some populations over others. Significant among‐population variation in seed germination requirements may, in part, explain shifts in source population representation in the production and restoration sites.